Eco-Innovation and SME Performance in Time of Covid-19 Pandemic: Moderating Role of Environmental Collaboration - Gusti N. Achmad; Rizky Yudaruddin; Puput W. Budiman; Eka Nor Santi; . Suharsono; Adi H. Purnomo; Noor Wahyuningsih (Emerging Science Journal, 2023)
Objectives: All businesses worldwide, especially small and medium-sized organizations, are now concerned about environmental degradation. Eco-innovation and environmental collaboration are expected to be the driving forces for saving the environment and the performance of companies. Therefore, this study aimed to ascertain how eco-innovation and environmental cooperation affect the financial, social, and environmental performance of SMEs. This study also explored environmental collaboration as a moderating variable for the effect of eco-innovation on the performance of SMEs. Methods/Analysis: Data from 300 small and medium-sized enterprises of Creative Home Décor were analyzed using structural equation modeling. Findings: Eco-innovation is necessary to improve the performance of Indonesia's SMEs. Environmental collaboration has a beneficial and substantial effect on the performance of the environment and society. Regarding environmental collaboration as a moderating variable, this study identified a positive and statistically significant coefficient regulating the relationship between financial performance and eco-innovation. Novelty /Improvement. The novelty of this research lies in its focus on the impact of eco-innovation and environmental collaboration on the performance of SMEs, particularly in developing countries such as Indonesia, during the COVID-19 pandemic. The study also contributed to the theoretical and empirical understanding of eco-innovation in developing countries and highlighted the importance of environmental collaboration in enhancing the social and environmental performance of SMEs. Additionally, this paper provided empirical and theoretical contributions on the role of environmental collaboration as a moderating variable that is particularly improving the performance of Indonesia's SMEs in Creative Home Décor during the COVID-19 pandemic.JEL Classifications: M12, L68, L25, L53, Q56 Doi: 10.28991/ESJ-2023-SPER-018 Full Text: PDF